Metrics used to analyze native advertising in Spanish media - Zomeño Jiménez, Daniel; Pallarés Renau, María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
For tactical purposes or a strategic vision of the use of native advertising, media and brands must work together to establish indicators to reliably analyze Return on Investment. This qualitative research seeks to define, through in-depth interviews with 16 Branded Content Directors from 15 groups or media, the metrics used by brands to determine the effectiveness of these actions in the media. Understanding how the media and advertisers define KPIs is crucial to delve into the relevance of the phenomenon and its consolidation as an alternative to more intrusive advertising.